THE EFFECT OF BRAND IMAGE, PRICE PERCEPTION, AND PROMOTION ON PURCHASE DECISION AT PIZZA HUT IN MANADO - Senduk, Indri F. A; Tulung, Joy E.; Arie, Fitty Valdie (Universitas Sam Ratulangi, 2021)
Changes in people's consumption patterns and the prospects for the fast-food restaurant industry can cause companies that appear in the food industry to become more competitive. The cultural shift of Indonesian society is increasingly modern, especially in urban areas that like practical and instant food. Changes in the culture of Indonesian society are usually marked by changes in lifestyle. The increasingly modern lifestyle of urban communities makes it difficult for people to avoid fast food types. Pizza Hut is a company engaged in fast food in the form of Italian-American cuisine with the main product being Pizza. Brand image is a very important thing that must be considered by companies as producers because a good brand image will create emotional value in consumers. Products sold by a company or producer must consider the price sold to the market, including discount prices offered to consumers, because consumers will judge the price of a product based on perceived benefits. The purpose of this study was to determine whether the influence of Brand Image, Price Perception, and Promotion on Purchase Decisions at Pizza Hut. This study uses quantitative methods. To achieve this goal, the researcher distributed questionnaires and the sample used was 99 respondents. The results of this study indicate that brand image, price perception, and promotion have a significant positive effect on purchase decisions.Â Keywords: brand image, price perception, promotion, purchase decision